Strategies for e-business : creating value through electronic and mobile commerce : concepts and cases /: creating value through electronic and mobile commerce : concepts and cases. (2014) - Jelassi, Tawfik, 1957-; Enders, Albrecht; Martínez-López, Francisco J (Francisco José)
No abstract available